Safety and accuracy of cannulated versus non-cannulated iliac screws: Cohort study - Yılar, Sinan; Toy, Serdar; Zencirli, Kemal (Journal of Surgery and Medicine, 2020)
Aim: Fixation with iliac screw is often used in long-segment instrumentation with lumbosacral fusion. Polyaxial screws are sent with fluoroscopy, computerized tomography, and navigation, or by freehand. In our study, we compared the accuracy of the cannulated iliac screw (CAS) and classic iliac screw (CLS) sent under fluoroscopy. Methods: This study was planned as a cohort study. Patients who underwent long segment fusion and sacroiliac fixation in our clinic between 2015 and 2018 were included in our study. The follow-up period of the patients was at least one year. All radiological and clinical data of patients were followed. Computerized tomographies obtained in the postoperative period were used to investigate the accuracy of the screws. Malposition of the screws was classified as medial, lateral and anterior perforation. Results: Sixty-six iliac screws of 29 patients who met the study criteria were evaluated. There were 15 patients (34 screws) in the classical screw group and 14 patients (32 screws) in the cannulated screw group. The classic screw group had two screws (one medial, one lateral) malpositioned, while the cannulated screw group had no screw malpositions. There was no statistically significant difference between the two groups. No complications were encountered in both groups during the intraoperative and postoperative periods. While two screws loosening was observed in the CLS group, one screw loosening was observed in the CAS group. No statistically significant difference was found. There was no screw breakage in either group. Conclusion: The use of cannulated iliac screws for sacroiliac fixation is an effective and reliable treatment option.